Educating the younger generation in the spirit of military patriotism today - Pulatov Jalil Abdisalom oglu (Zien Journals, 2021)
At the present stage, the problem of educating the younger generation in the spirit of patriotism is one of the problems in pedagogy that needs the newly formed statehood and the unity of the people living in it. It is dialectically connected with the problems of international education, the features, values, ideals of the formation of national consciousness. In particular, the Law of the Republic of Kazakhstan "On Education" states: "The main task of the education system is to create the necessary conditions for the formation and development of the individual on the basis of national and universal values, scientific and practical achievements." We can see a rising example of patriotic values ​​in this legislation
Keywords: Spirit of Patriotism; Education System; Scientific and Practical Achievements; National and Universal Values